Utilization of Plastic Waste as an Additive Material in Concrete Mixtures: A Study on Compressive Strength and Material Sustainability - Muhammad Abdi Ridha (SEAN Institute, 2025)
This study investigates the incorporation of plastic waste as an additive in concrete mixtures, focusing on its effects on compressive strength and sustainability. Using a quantitative experimental approach, various proportions of plastic waste—specifically polypropylene (PP), polyethylene terephthalate (PET), low-density polyethylene (LDPE), and high-density polyethylene (HDPE)—were incorporated as partial replacements for fine or coarse aggregates. Concrete specimens were tested at 7, 14, and 28 days for compressive strength. Results indicate that while increasing plastic content generally reduces compressive strength, optimal low-percentage substitutions can maintain structural integrity and contribute to environmental sustainability by reducing plastic waste. This research supports the potential of plastic waste as a sustainable supplementary material in concrete production.